Sistem Pendukung Keputusan Pemilihan Konten Lokal Terbaik Menerapkan Metode Moosra (Studi Kasus: Komisi Penyiaran Indonesia) - Divya Febrina; Imam Saputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Decision support system as a computer-based system consisting of components including language system components, knowledge system components and problem processing system components that interact with one another, which helps decision making through the use of data and decision models to solve semi-structured and unstructured problems. This study uses the Moosra Method in Selecting the Best Local Content based on criteria by using a formula which results are more accurate and right on target. In it also all data are combined into one with the weight of the assessment that has been obtained through an assessment of the test results. The research conducted is to create a system that can provide consideration in making decisions for the selection of the best local content.